Effect of abdominal binders on breathing in tetraplegic patients. Issue 12 (December 1986) - Goldman, J M; Rose, L S; Williams, S J; Silver, J R; Denison, D M
Abstract : We studied the effect on breathing of a conventional and a newly designed abdominal binder in seven patients with complete tetraplegia. The indices of respiratory ability used were the transdiaphragmatic pressure on maximal sniff (sniff Pdi), the maximum static inspiratory mouth pressure (PImax), and the vital capacity (VC). These were measured in patients with and without binders, in the supine position, raised up to 70 degrees on a tilt table, and seated upright. When patients were raised from the supine to the 70 degrees tilt and to the seated posture, sniff Pdi and VC decreased. Both binders improved VC in the seated position and at 70 degrees tilt, and sniff Pdi at 70 degrees tilt. The new binder was as effective as but no better than the conventional binder. PImax was too variable to be a valuable index of inspiratory power. These findings support the view that abdominal binders assist breathing in tetraplegic patients who are seated or raised to near vertical positions.